The Communication Between the Immune and Nervous Systems: The Role of IL-1β in Synaptopathies - Pozzi, Davide; Menna, Elisabetta; Canzi, Alice; Desiato, Genni; Mantovani, Cristina; Matteoli, Michela (Frontiers in Molecular Neuroscience, 2018)
In the last fifteen years, groundbreaking genetic progress has underlined a convergence onto coherent synaptic pathways for most psychiatric and neurodevelopmental disorders, which are now collectively called “synaptopathies”. However, the modest size of inheritance detected so far indicate a multifactorial etiology for these disorders, underlining the key contribution of environmental effects to them. Inflammation is known to influence the risk and/or severity of a variety of synaptopathies. In particular, pro-inflammatory cytokines, produced and released in the brain by activated astrocytes and microglia, may play a pivotal role in these pathologies. Although the link between immune system activation and defects in cognitive processes is nowadays clearly established, the knowledge of the molecular mechanisms by which inflammatory mediators specifically hit synaptic components implicated in synaptopathies is still in its infancy. This review summarizes recent evidence showing that the pro-inflammatory cytokine IL-1β specifically targets synaptopathy molecular substrate, leading to memory defects and pathological processes. In particular we describe three specific pathways through which IL-1β affects (1) synaptic maintenance/dendritic complexity, (2) spine morphology and the (3) excitatory/inhibitory balance. We coin the term immune-synaptopathies to identify this class of diseases.